Jogos de empresas e percepção de aprendizagem de discentes de cursos técnicos integrados ao ensino médio - Sofiate, Eduardo (2024)
The aim of this dissertation is to investigate the use of business games as a teaching-learning tool in technical level courses integrated into secondary education. To achieve this objective, the study is structured in two articles. Article 1 aimed to explore the production of knowledge on business games applied to secondary and technical education, using literature review techniques. From the bibliometric analysis, a thematic map of the field emerged and the narrative review demonstrated the low density of publications on the subject of business games applied to secondary and technical education and divergences between the findings of these studies. Article 2 aimed to investigate the effect of business games on the perception of learning and satisfaction of students on technical level courses integrated into secondary education. To this end, a study was carried out with a sample made up of graduating students from the technical level courses in Administration integrated into secondary education at the Barra de São Francisco and Montanha campuses and graduating students from the technical level course in Logistics integrated into secondary education at the Viana campus of Ifes. The data was collected using a self-administered online questionnaire and analyzed using partial least squares structural equation modeling. The results showed a positive effect of the game experience on the students' perception of learning and satisfaction and the hypothesis of the existence of a halo effect was rejected.